Upaya Penurunan Jumlah Breakdown dengan Metode Reliability Centered Maintenance di PT. Sentosa Laju Sejahtera Site SLS-Bosowa - Elian Sasmita Wijaya; Kriswanto Widiawan (Jurnal Titra, 2023)
PT. Sentosa Laju Sejahtera is a contracting company engaged in coal and mineral mining industry. PT. Sentosa Laju Sejahtera is facing low reliability problem due to a high rate of functional failures. To address this issue, a study was conducted using Reliability Centered Maintenance (RCM. The goal of RCM is to determine the best type of maintenance. RCM is assisted by two other methods, namely Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA). FMEA aims to identify the models that has highest number of failures and rank them based on the highest risk value. Model AXOR 2528CH had the highest number of failures, with 2416 failures or 47% of all models. The two main causes were tyre component and brake system component. FTA aims to identify the root causes of problems related to the method, man, material, machine, measurement, and environment factors. The proposed solutions include implementing tyre inspection, ensuring consistency in brand selection, and creating tyre report. These proposed solutions have resulted in a decrease of 23.5% in the number of functional failures of the tyre components compared to April 2022 and an increase of 50.68% in the average duration of tyre component failures.